2002
DOI: 10.3354/dao050067
|View full text |Cite
|
Sign up to set email alerts
|

Two epizootic diseases in Chesapeake Bay commercial clams, Mya arenaria and Tagelus plebeius

Abstract: Declining Chesapeake Bay harvests of softshell clams, together with historical and emerging reports of epizootic diseases in Mya arenaria, prompted a survey in summer 2000 of the health status of selected commercial clam populations. All sampled populations (8 M. arenaria softshell clam, 2 Tagelus plebeius razor clam) were infected by Perkinsus sp. protozoans at prevalences ranging from 30 to 100% of sampled clams. Nucleotide sequences for the internal transcribed spacer (ITS) region of the rRNA gene complex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 29 publications
3
86
2
Order By: Relevance
“…17). A recent study, however, has reported that ITS sequences previously thought to distinguish P. chesapeaki and P. andrewsi are really ITS variants that can both be found in a single clonal isolate culture (Dungan et al 2002). This result suggests that P. chesapeaki and P. andrewsi are the same species of Perkinsus.…”
Section: Discussioncontrasting
confidence: 42%
“…17). A recent study, however, has reported that ITS sequences previously thought to distinguish P. chesapeaki and P. andrewsi are really ITS variants that can both be found in a single clonal isolate culture (Dungan et al 2002). This result suggests that P. chesapeaki and P. andrewsi are the same species of Perkinsus.…”
Section: Discussioncontrasting
confidence: 42%
“…protozoans, have been documented in this species on the Atlantic west coast (Brousseau & Baglivo, 1991;Dungan et al, 2002;Earle & Crisley, 1975 (Perez, 2011;Ruiz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, Perkinsus spp. can infect several alternate hosts in addition to the type host, and this is especially true for P. olseni (Kotob et al 1999, Dungan et al 2002, Bower & McGladdery 2003.…”
Section: Introductionmentioning
confidence: 99%
“…P. marinus was the first species of the genus to be described and was reported as the causative agent of mortalities of Crassostrea virginica in the Gulf of Mexico (Mackin et al 1950). Since the synonymy between P. olseni and P. atlanticus (Goggin 1994, Robledo et al 1999a, Murrell et al 2002, Cremonte et al 2005) and between P. chesapeaki and P. andrewsi (Dungan et al 2002, Burreson et al 2005 has been described, the remaining species of the genus are P. qugwadi in Patinopecten yessoensis (Blackbourn et al 1998), Perkinsus mediterraneus in Ostrea edulis (Casas et al 2004), and P. honshuensis in Ruditapes philippinarum (Dungan et al 2006); recently, P. behaensis has been described in oysters from China (Moss et al 2008). However, Perkinsus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation